A new two-mode thermo- and squeezing-mixed optical field - 周军 范洪义 宋军 (Chinese physics B, 2017)
We propose a new two-mode thermo-and squeezing-mixed optical field, described by the new density operator ρ=1-e^f-｜g｜^2 e^ga^＋b^＋e^fa^＋a｜0〉 f_（bb） 〈0｜ e~（g＊ab）, where ｜0〉_（bb） 〈0｜ is the b-mode vacuum, e ^fa^＋arepresents the thermo-field, and e^ga^＋b^＋ indicates squeezing. The photon statistics for ρ is studied by virtue of the method of integration within ordered product（IWOP） of operators. Such a field can be generated when a two-mode squeezed state passes through a one-mode dissipation channel.